VITAMIN A AND E LEVELS IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Aksoy, Aziz; Gozel, Nevzat; Bulut-Arikan, Funda; Kucuksu, Mehmet; Ozdemir, Fethi Ahmet (Parlar Scientific Publications (P S P), 2018)
Chronic kidney disease (CKD) is a disease that manifests itself with abnormalities in kidney structure or function. Inflammation and oxidative stress increase in kidney disease in parallel with the advancement of the disease. In addition, vitamin synthesis metabolism is also disrupted as a result of the decrease in kidney functions. Vitamins A and E are strong anti-inflammatories and antioxidants which protect the body against oxidative stress. Hence, the activation of these vitamins in CKD patients is of significant importance. The study was carried out with the participation of 139 people comprised of 79 volunteer patients diagnosed with Stage-5 CKD and 60 healthy volunteers (control). Demographic measurements of the participants were carried out and their biochemical parameters (glucose, urea, creatinin, AST, ALT, and LDL etc.) were determined via ELISA and spectrophotometric analyses. Serum A and E vitamin levels were determined via HPLC analysis. No statistically significant difference was determined (p=0,56) in this study between the groups even though the vitamin A level of the patient group was lower, while vitamin E levels were determined to be lower at a statistically significant level in the patient group in comparison with the control group (about half) (p=0,000).Statistically significant differences were determined between the patient and control groups when; BMI, glucose, urea, creatinin, AST, ALT, LDL, triglyceride, HDL, albumin, hemoglobin, platelet, RBC, HCT, MCH and Diastolic blood pressure averages were compared (p > 0,005). A positive and statistically significant correlation was determined in the patient group between Vitamin A and E and urea (r=0,325 p=0,003; r=0,278, p=0.013). The decrease in vitamins A and E levels in CKD may be increasing oxidative stress and inflammation in these patients. It can be concluded as a result of this study that a low dose of vitamin A and a strong dose of vitamin E work as strong antioxidants in chronic kidney disease as strong antioxidant and anti-inflammatory molecule.
Keywords: Chronic kidney disease; Vitamin A; Vitamin E; ELISA; HPLC